2022
DOI: 10.1002/ajmg.a.63059
|View full text |Cite
|
Sign up to set email alerts
|

Personal social networks of people with Down syndrome

Abstract: Studies in the neurotypical population have demonstrated that personal social networks can mitigate cognitive decline and the development of Alzheimer disease. To assess whether these benefits can also be extended to people with Down syndrome (DS), we studied whether and how personal networks can be measured in this population. We adapted a personal networks instrument previously created, validated, and implemented for the neurotypical population. We created two versions of the survey: one for participants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Another explanation could be that insufficient time had transpired from the end of pandemic restrictions. Even after the state of Previous research demonstrated that self-reported assessments of social networks matched proxy-reported assessments (Skotko et al, 2023). At this follow-up time point, this was the case for mostbut not all-measures.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Another explanation could be that insufficient time had transpired from the end of pandemic restrictions. Even after the state of Previous research demonstrated that self-reported assessments of social networks matched proxy-reported assessments (Skotko et al, 2023). At this follow-up time point, this was the case for mostbut not all-measures.…”
Section: Discussionmentioning
confidence: 69%
“…Our survey for both the study partners and people with DS was adapted from the PERSNET personal networks instrument (Dhand et al, 2016(Dhand et al, , 2018Prust et al, 2021) and is previously described (Skotko et al, 2023). In short, the survey elicited the names of people with whom the person with DS "discussed important stuff with," "hung out with," and sought help from when they felt sick (please see Supplementary Materials of Skotko et al, 2023, for a copy of the survey). Names were then unduplicated.…”
Section: Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Improving social networks for people with IDDs has far reaching benefits. For instance, expanding social personal networks of people with Down syndrome can mitigate cognitive decline and the development of Alzheimer’s disease [55].…”
Section: Discussionmentioning
confidence: 99%
“…Improving social networks for people with IDDs has far reaching benefits. For instance, expanding social personal networks of people with Down syndrome can mitigate cognitive decline and the development of Alzheimer's disease [55]. Many IDDs-transition specialists suggest that coordination with either postsecondary education institutions or local agencies that provide employment support can provide bridges to a more self-determined and secure future [52,53,56].…”
Section: Discussionmentioning
confidence: 99%